ON A SOLUTIONS OF ONE CLASS OF ALMOST HYPOELLIPTIC EQUATIONS - Hakobyan, G.H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
We prove that if $P(D)=P(D_1,D_2)=\sum_αγ_α D_1^{α_1}D_2^{α_2}$ is almost hippoelliptic regular operator, then for enough small $δ>0$, all solutions of equation $P(D)u=0$ from $L_{2,δ}(R^2)$ are entire analytical functions.
Keywords: almost hypoelliptic operator (polynom), weighted Sobolev spaces, analyticity of solution